The Effect of Receivables Turnover Ratio and Current Assets Turnover Ratio on Own Capital Profitability at PT. Alfa Scorpii Sibolga - Denisa Gea; Safriadi Pohan; Rahmadiah Hanum (Sean Institute, 2024)
This research aims to determine whether the receivables turnover ratio (X1) and the current assets turnover ratio (X2) either partially or simultaneously have a significant effect on the profitability of own capital at PT. Alfa Scorpii Sibolga. The data analysis methods used are classical assumption testing, multiple linear regression analysis and hypothesis testing. The data used in this research is secondary data, by collecting PT financial reports. Alfa Scorpii Sibolga which consists of a balance sheet and profit and loss report for 2018 to 2022. The sample used in this research is a financial report in the form of a balance sheet and profit and loss report of PT. Alfa Scorpii Sibolga 2018 - 2022. The results of the F test, obtained a calculated F value of 0.420 with a significant level of 0.704, meaning that simultaneously (simultaneously) the receivables turnover ratio and the current assets turnover ratio have an insignificant effect on the profitability of own capital. Partial t test results shows the level of significance obtained from the independent variables, namely the receivables turnover ratio of -0.900 and the ratio of current assets turnover to own capital profitability of 0.463. This shows that the receivables turnover ratio has an insignificant negative effect and the current assets turnover ratio has an insignificant positive effect on the profitability of own capital. Based on the research results, the researcher suggests that investors should pay attention to the value of the receivables turnover ratio and current assets turnover ratio before making a decision to invest, and companies should pay attention to the management of receivables and current assets by paying attention to the receivables turnover ratio and current assets turnover ratio to make it more effective and efficient so as to achieve maximum profits.